ALIH KODE DAN CAMPUR KODE PADA INTERAKSI WARGA MTS BABUSSALAM KECAMATAN TELUK PAKEDAI KABUPATEN KUBU RAYA - Elviana, Elviana; Simanjuntak, Hotma; Wartiningsih, Agus; Susissusiawan, Ahadi; Sanulita, Henny Sanulita (Jurnal Kajian Pembelajaran dan Keilmuan, 2024)
The use of the Indonesian language is a cultural development nation, as well as the unifying language of the Indonesian na Today most of humanity is bilingual. Bilingual symptoms can o anytime and anywhere. One of them is in the educational environm The educational environment is one of the formal places w Indonesian is supposed to be used. However, in reality there are m uses of the Madurese language either intentionally or unintentio by students and teachers. This language condition is a sympto code-switching and code-mixing that is spoken by students students when interacting both in class and outside the classroom. purpose of this study was to describe the types, forms and factors cause code-switching and code-mixing in the residents of Babussalam, Teluk Pakedai District, Kubu Raya Regency. The me in this article uses a descriptive method. The form of research use this research is qualitative research. The data collection technique the researcher used in this study was a direct communica technique, namely interviews and an indirect technique, na indirect observation. Data collection tools that researchers use recording devices and note-taking devices. This study uses equivalent method with the technique of sorting out the determina